Heart Failure With Mid-range Ejection Fraction: Every Coin Has Two Sides - Zhu, Kaiyuan; Ma, Teng; Su, Yang; Pan, Xin; Huang, Rongrong; Zhang, Fenglei; Yan, Chunxi; Xu, Dachun (Frontiers in Cardiovascular Medicine, 2021)
This review summarizes current knowledge regarding clinical epidemiology, pathophysiology, and prognosis for patients with HFmrEF in comparison to two other well-studied HF groups. Although recommended treatments currently focus on aggressive management of comorbidities, we summarize potentially beneficial therapies. Future studies are needed to more clearly characterize HF and to identify effective management strategies that can reduce the high cardiovascular morbidity and mortality of patients with this HF phenotype.